2014
DOI: 10.1016/j.dci.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow trout (Oncorhynchus mykiss) contain two calnexin genes which encode distinct proteins

Abstract: Calnexin (IP90/P88) is an integral membrane protein of the endoplasmic reticulum that binds newly synthesized N-linked glycoproteins during their folding in the ER including MHC class I molecule. This manuscript reports the identification of two unique cDNA clones of calnexin in rainbow trout. Both encode putative mature proteins of 579 and 592 aa respectively in addition to a 24 aa signal peptide. Sequence analysis revealed that only one of the two cDNA clones encodes a putative ER retention signal, K/QEDDL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Both genes display fair expression in immunologically important tissues such as head kidney and spleen as well as other organs such as brain and ovary (Table 2 ). This gene duplication has previously been identified in trout [ 50 ] and is a remnant of the SGD displaying high sequence identity between paralogs. If one or both copies serve the classical MHCIa molecules remains to be established.…”
Section: Resultsmentioning
confidence: 94%
“…Both genes display fair expression in immunologically important tissues such as head kidney and spleen as well as other organs such as brain and ovary (Table 2 ). This gene duplication has previously been identified in trout [ 50 ] and is a remnant of the SGD displaying high sequence identity between paralogs. If one or both copies serve the classical MHCIa molecules remains to be established.…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure 13, our transcriptome profiling identified several R. salmoninarum-responsive transcripts involved in antigen-presenting and processing pathways. The teleost MH-I-dependent pathway exhibits several differences with their mammalian counterparts (123)(124)(125)(126)(127)(128); for example, different paralogues (i.e., Calnexin) and splice variants (i.e., Tapasin) of molecules involved in the MH-I pathway were identified and suggested to play diverged or unique roles in salmonid antigen presentation (123)(124)(125)(126)(127)(128). The qPCR results showed the R. salmoninarum-dependent up-regulation of fcgr1 and tnfsf14, as well as down-regulation of cdh1, flrt3, and ndrg2 (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, MHC II expression is downregulated at 2°C—but not 5°C—in rainbow trout cells, suggesting a susceptibility to bacterial diseases during cold stress [ 66 ]. Recent studies have identified, characterized and produced polyclonal antibodies to rainbow trout genes involved in the antigen processing pathway (APP) including MHC I [ 67 ], β 2 M [ 64 ], TAP1/2 [ 68 ] tapasin [ 69 ], calreticulin [ 70 , 71 ], ERp57 [ 72 ] and calnexin [ 73 ]. Collectively, these studies demonstrate the largely conserved nature of the APP in rainbow trout.…”
Section: Innate Immunity and Temperaturementioning
confidence: 99%